Nominal Clauses in Popular Scientific Style - Kožená, Michaela (Univerzita Pardubice, 2012)
This Bachelor paper focuses on the occurence of nominal clauses in popular-scientific literature, as well as their Czech translation. Firstly, the term 'subordinate clause', sentence elements, and types of nominal clauses are introduced. Then the popular-scientific style is described and the differences between Czech and English are briefly discussed. Finally, the corpus of examples for the analysis is presentend, analysed and discussed.
Nominální věty v populárně naučné literatuře
Keywords: věta podřazená; nominální věty; finitní a nefinitní tvary; nominální angličtina; verbální čeština; populárně naučný styl; český překlad; subordinate clause; nominal clauses; finite and non-finite form; nominal English; verbal Czech; popular-scientific style; Czech translation